Molecular dynamics simulations for the growth of CH4-CO2 mixed hydrate - Yi, Lizhi; Liang, Deqing; Zhou, Xuebing; Li, Dongliang (Journal of Energy Chemistry, 2014)
Molecular dynamics simulations are performed to study the growth mechanism of CH4-CO2 mixed hydrate in (CO2)-C-x = 75%, (CO2)-C-x = 50%, and (CO2)-C-x = 25% systems at T = 250 K, 255 K and 260 K, respectively. Our simulation results show that the growth rate of CH4-CO2 mixed hydrate increases as the CO2 concentration in the initial solution phase increases and the temperature decreases. Via hydrate formation, the composition of CO2 in hydrate phase is higher than that in initial solution phase and the encaging capacity of CO2 in hydrates increases with the decrease in temperature. By analysis of the cage occupancy ratio of CH4 molecules and CO2 molecules in large cages to small cages, we find that CO2 molecules are preferably encaged into the large cages of the hydrate crystal as compared with CH4 molecules. Interestingly, CH4 molecules and CO2 molecules frequently replace with each other in some particular cage sites adjacent to hydrate/solution interface during the crystal growth process. These two species of guest molecules eventually act to stabilize the newly formed hydrates, with CO2 molecules occupying large cages and CH4 molecules occupying small cages in hydrate.